1990
DOI: 10.2176/nmc.30.451
|View full text |Cite
|
Sign up to set email alerts
|

Measurement of Energy Expenditure in Acute Stage of Cerebrovascular Diseases

Abstract: Oxygen consumption (VO2), carbon dioxide production, respiratory quotient, urinary nitrogen excretion (UN), resting energy expenditure (REE), REE rate (%REE) and consumption rates of carbohydrate (%C), fat (%F) and protein (%P) were pre- and postoperatively measured in the acute stage of 17 patients with cerebrovascular diseases. They included six of ruptured intracranial aneurysms, six of cerebrovascular occlusion, and five of hypertensive intracerebral hemorrhage. Preoperative VO2, UN, REE, and %REE were 185… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2007
2007
2019
2019

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 30 publications
0
4
0
Order By: Relevance
“…However, they are derived from energy requirements of normal healthy people for basal metabolism, physical activity, thermogenesis and tissue synthesis (Department of Health, 1991) and their appropriateness for acute stroke patients remains unclear. Increased REE rates have been reported in some critically ill stroke patients, although other studies have not observed any significant difference between measured (by indirect calorimetry) and predicted rates in stroke patients up to 90 days after admission (Touho et al. , 1990; Weekes & Elia, 1992; Finestone et al.…”
Section: Discussionmentioning
confidence: 90%
“…However, they are derived from energy requirements of normal healthy people for basal metabolism, physical activity, thermogenesis and tissue synthesis (Department of Health, 1991) and their appropriateness for acute stroke patients remains unclear. Increased REE rates have been reported in some critically ill stroke patients, although other studies have not observed any significant difference between measured (by indirect calorimetry) and predicted rates in stroke patients up to 90 days after admission (Touho et al. , 1990; Weekes & Elia, 1992; Finestone et al.…”
Section: Discussionmentioning
confidence: 90%
“…Measurements with IC on patients with hemorrhagic stroke have been reported. In most of these studies, single short measurements have been performed once or twice during the acute stage of the disease (9)(10)(11)(12)(13)(14). In patients with SAH, measured EE has generally then been elevated compared to the energy demand predicted by equations.…”
Section: Introductionmentioning
confidence: 99%
“…For many patient groups, however, there is a general lack of studies from which to make any useful recommendations. Despite the high prevalence of cerebro-vascular accident, a literature review reveals only four studies in which energy expenditure has been measured post-cerebro-vascular accident, two in ischaemic strokes (Weekes & Elia, 1992; Finestone et al 2003) and the other two in haemorrhagic strokes (Piek et al 1989; Touho et al 1990). Another area requiring more research is the effect of abnormal losses, e.g.…”
Section: Discussionmentioning
confidence: 99%